A Literature Analysis of “Kering” By Iwan Simatupang - Rosmani Sianipar (JOMANTARA, 2022)
Iwan Simatupang the great writer was born on January 18, 1928. Lots of his works have been translated into various languages, while the demand for reprints continues to increase. Iwan Simatupang's "Kering" is not only in a physical sense but is more contemplative in nature. With the adventures carried out, he describes how the actors are afflicted with psychological, spiritual, ideas, and ready to be swallowed by termites so that it becomes pathetic. Iwan, in channelling his ideas and thoughts is by the understanding of the philosophers he admires, namely existentialist philosophers. Iwan can also be called a nihilist. He negates all old values ​​and confirms standard values. He tried to overcome something he felt was an obstacle in the creation of his writing. The flow of thoughts he emits in a firm, yet artistic form. This is most evident in the novel 'Kering'. He ignores the rules, neither in his life nor in formulating his thoughts. If people want to characterize the nature of his mind and wisdom, it is fierce, like a sailboat hit by the waves of the ocean.